Drymarchon corais (Colubridae) and Caiman crocodilus (Alligatoridae) use different feeding behaviors to consume poisonous toads - Oda, Fabrício; Signorelli, Luciana; Souza, Franciele; Souza, Valter; Almeida, Waltécio; Pereira, Luana; Morais, Alessandro (Dryad, 2022)
Drymarchon corais and Caiman crocodilus are reported here using different
feeding behaviors for consuming poisonous toads of the genus Rhinella
(Bufonidae). Drymarchon corais was observed feeding on specimens of
Rhinella diptycha without avoiding contact with the parotoid macroglands,
suggesting that this snake species is immune to toad toxins. Caiman
crocodilus was recorded avoiding contact with the parotoid macroglands of
specimens of Rhinella marina by consuming only the front and rear legs,
suggesting that this caiman may be sensitive to toad toxins. Further
experimental and field studies are needed to better understand the feeding
behavior of D. corais and C. crocodilus, and the effects of Rhinella
toxins on these predators.
Records of predation on R. diptycha and R. marina were obtained from
occasional observations in nature at a locality in the municipality of
Campina Verde of the state of Minas Gerais (MG), a locality in the
municipality of Sambaíba of the state of Maranhão (MA), and a locality in
the municipality of Manaus of the state of Amazonas (AM), in the
Southeast, Northeast and North regions of Brazil, respectively.
Keywords: FOS: Natural sciences